2012
DOI: 10.1186/1471-2458-12-897
|View full text |Cite
|
Sign up to set email alerts
|

Effects of being uninsured or underinsured and living in extremely poor neighborhoods on colon cancer care and survival in California: historical cohort analysis, 1996—2011

Abstract: BackgroundWe examined the mediating effects of health insurance on poverty-colon cancer care and survival relationships and the moderating effects of poverty on health insurance-colon cancer care and survival relationships among women and men in California.MethodsWe analyzed registry data for 3,291 women and 3,009 men diagnosed with colon cancer between 1996 and 2000 and followed until 2011 on lymph node investigation, stage at diagnosis, surgery, chemotherapy, wait times and survival. We obtained socioeconomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 69 publications
2
40
1
1
Order By: Relevance
“…Second, in the United States, people with private HI or Medicare coverage are more likely to receive the best, evidencebased care and to survive longer than are those with arguably less adequate Medicaid coverage or no coverage (Boland et al, 2013;Bradley, Given, Dahman, & Fitzgerald, 2008). Third, being poor, uninsured or Medicaid insured are all much more common among women than men in the United States (Gorey et al, 2012;DeNavas-Walt et al, 2012;Iceland, 2013). And fourth, HI has recently been found to substantially buffer the disadvantaging effects of poverty on colon cancer treatment and survival among women, but not men, in California (Gorey et al, 2012).…”
Section: Colon Cancer Care In Poor Us and Canadian Neighborhoodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Second, in the United States, people with private HI or Medicare coverage are more likely to receive the best, evidencebased care and to survive longer than are those with arguably less adequate Medicaid coverage or no coverage (Boland et al, 2013;Bradley, Given, Dahman, & Fitzgerald, 2008). Third, being poor, uninsured or Medicaid insured are all much more common among women than men in the United States (Gorey et al, 2012;DeNavas-Walt et al, 2012;Iceland, 2013). And fourth, HI has recently been found to substantially buffer the disadvantaging effects of poverty on colon cancer treatment and survival among women, but not men, in California (Gorey et al, 2012).…”
Section: Colon Cancer Care In Poor Us and Canadian Neighborhoodsmentioning
confidence: 99%
“…Third, being poor, uninsured or Medicaid insured are all much more common among women than men in the United States (Gorey et al, 2012;DeNavas-Walt et al, 2012;Iceland, 2013). And fourth, HI has recently been found to substantially buffer the disadvantaging effects of poverty on colon cancer treatment and survival among women, but not men, in California (Gorey et al, 2012). Colon cancer care seems quite sensitive to the sorts of social policy forces that probably determine much of the income and HI inequities, particularly among women, in North America.…”
Section: Colon Cancer Care In Poor Us and Canadian Neighborhoodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study found that Medicaid acts as a suppressor of racial disparities in health for children with special needs (Rose et al 2010). Gorey et al (2012) investigated the relationship between poverty, health insurance coverage, and quality of care received in patients with colon cancer. They reported that insurance mediates the quality of cancer care received and that living in poor neighborhoods moderates this effect.…”
Section: Mediation Analysis In Health Services Researchmentioning
confidence: 99%